Korelasi Motilitas Progresif dan Keutuhan Membran Sperma dalam Semen Beku Sapi Ongole Terhadap Keberhasilan Inseminasi - Jalius, Jalius; Depison, Depison (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The correlation between the progressive motility and sperm membrane totality  in frozen semen of Ongole with artificial insemination success. This  experiment was aimed to evaluated the characteristics of progressive  motility  and  spermatozoa  membrane    totality  of Ongole  cattle in  frozen  semen  and  their correlation  to  the successful of artificial  insemination.  The  parameters  were  progressive  motility  and membrane totality (MT) successful of artificial insemination was measured by non return rate (NR)  and  conception  rate  (CR). Result  of  this  experiment  showed  that  PM  =  38.14%,  MT  =  69.86%,  NR  = 64.49% and CR = 53.47%. Progressive mortality  significantly influenced (P<0.05) NR. Mortality  and  membrane  totality    significantly  determine  (P<0.05)  the successful  of  artificial  insemination  (CR)  of Ongole cattle